Relação entre os parâmetros periodontais e de controle glicêmico em pacientes com diabetes mellitus tipo 2 - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
Periodontal disease (PD) and diabetes mellitus (DM) are high prevalent chronic diseases in the adult population worldwide. There is evidence of bidirectional relationship between both diseases, i.e., DM represents a risk factor for PD and PD can impair diabetes control, resulting in a cycle of cause and effect with harmful consequences to the health of individuals. This cross-sectional study aimed to determine the socioeconomic profile of the diabetic population registered in Hiperdia program in the city of Manaus, Amazonas and to measure their periodontal status, looking for a possible relationship between periodontal and glycemic control parameters. A total of 209 type 2 diabetic patients participated of the survey, which consisted of three stages: interview, physical and periodontal examination and laboratorial tests. Data were analysed using the software Stata SE version 10.1. Chi-square tests, Spearman’s correlation, bivariate analysis and multivariate logistic regression were applied. The study population presented a mean age of 55 years, with majority of females, mixed race, income of 1-3 times the minimum wage, complete high school, average of 8 years of DM, most of them were hypertensive and 37.8% had other comorbidities, such as nephropathy and retinopathy; the average fasting plasma glycemia (FPG) and glycated hemoglobin (HbA1c) were 181.96 mg/dL and 7.92%, respectively. There was a significant positive correlation between HbA1c and plaque index - PI (r = 0.31; p <0.001), gingival index - GI (r = 0.24; p <0.001), probing depth - PD (r = 0, 19; p = 0.007) and clinical attachment level - CAL (r = 0.23; p <0.001) and between the FPG and PI (r = 0.42; p <0.001), GI (r = 0.37; p <0.001), PD (r = 0.30; p <0.001), CAL (r = 0.26 p <0.001) and dental mobility (r = 0.14; p = 0.031). Individuals diagnosed with periodontitis (208) were divided into two groups: mild/moderate periodontitis and severe periodontitis. In the bivariate analysis, it was verified association between the variables: age ≥ 50 years (p = 0.019), more than 2 years of no dental care (p = 0.021), not flossing (p = 0.039), time with DM> 4 years (p = 0.013), GI and PI ≥ 50% (p <0.001 and p = 0.003), HbA1c ≥ 9% (p <0.001) and FPG> 110 mg/dL (p <0.001) like risk factors and sex female (p = 0.025), ), 9-12 years of study (p = 0.025), ), not using insulin (p = 0.032) like protection factors in the severe periodontitis outcome. After multivariate logistic regression, it was observed that age ≥ 50 years (OR = 2.36; CI: [1.10 to 5.04]; p = 0.027) and HbA1c ≥ 9% (OR = 9.05; CI: [2.98 to 27.51 ]; p <0.001) are risk factors and female gender (OR = 0.47; CI: [from 0.23 to 0.99]; p = 0.047), 9-12 years of education (OR = 0.51; CI: [0.17 to 1.69]; p = 0.287) and no use insulin (OR = 0.33; CI: [from 0.12 to 0.85]; p = 0.023) are protector factors for severe periodontitis. It was concluded that individuals with HbA1c ≥ 9% are 9.05 times more likely to have severe periodontitis and that, considering the high prevalence of PD in diabetics and the significant correlation between periodontal and glycemic control parameters, it is required greater attention on the oral health of diabetics.
Keywords: Doença Periodontal; Diabetes Melittus tipo 2; Parâmetros periodontais; Parâmetros de controle glicêmico; Hemoglobina glicada; Controle do diabetes; Periodontal disease; Glycated haemoglobin; CIÊNCIAS DA SAÚDE: ODONTOLOGIA